Age Differences in Dual-Task Performance After Practice. - Göthe, Katrin; Oberauer, Klaus; Kliegel, Reinhold (Psychology & Aging, 2007)
This study investigated whether older adults could acquire the ability to perform 2 cognitive operations in parallel in a paradigm in which young adults had been shown to be able to do so (K. Oberauer & R. Kliegl, 2004). Twelve young and 12 older adults practiced a numerical and a visuospatial continuous memory updating task in single-task and dual-task conditions for 16 to 24 sessions. After practice, 9 young adults were able to process the 2 tasks without dual-task costs, but none of the older adults had reached the criterion of parallel processing. The results suggest a qualitative difference between young and older adults in how they approach dual-task situations. Reprinted by permission of the publisher.